2000
DOI: 10.1074/jbc.275.7.4759
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Processing of Endogenously Synthesized ApoE on the Macrophage Cell Surface

Abstract: We have previously established the presence of a pool of apoE sequestered on the macrophage cell surface by demonstrating its displacement from a cell monolayer at 4°C. In this series of experiments, we use a cell surface biotinylation protocol to directly quantitate apoE on the macrophage cell surface and evaluate its transport to and from this cell surface pool. In human monocytederived macrophages labeled to equilibrium and in a mouse macrophage cell line transfected to constitutively express human apoE3, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 25 publications
2
54
1
Order By: Relevance
“…We evaluated this possibility by examining the time course of the oleic acid induction of apoE secretion. As shown in Table II, a substantial induction of apoE secretion by fatty acid required at least 6 h. This result argues against simple displacement of a cell surface pool of apoE by fatty acid as a mechanism for increased apoE secretion as we have previously shown that the half-life of apoE on the cell surface of macrophages is ϳ12 min (32). Further, the 6-h lag suggests that some homeostatic alteration in cells is necessary before apoE secretion is increased.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…We evaluated this possibility by examining the time course of the oleic acid induction of apoE secretion. As shown in Table II, a substantial induction of apoE secretion by fatty acid required at least 6 h. This result argues against simple displacement of a cell surface pool of apoE by fatty acid as a mechanism for increased apoE secretion as we have previously shown that the half-life of apoE on the cell surface of macrophages is ϳ12 min (32). Further, the 6-h lag suggests that some homeostatic alteration in cells is necessary before apoE secretion is increased.…”
Section: Resultsmentioning
confidence: 77%
“…Therefore, it is unlikely that the effect of oleic acid on apoE secretion is mediated via changes in cellular sterol trafficking. We have also previously reported that apoE can be sequestered on the macrophage cell surface prior to secretion and may, in fact, undergo recycling through intracellular compartments prior to secretion (31,32). We therefore considered the possibility that exogenous fatty acids could displace apoE from the cell surface and thus produce the simultaneous increase in medium apoE and decrease in cellular apoE that we observed in pulse-chase experiments.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Twenty g of cell lysate or 25 l of medium were resolved by 10% SDS-PAGE and electroblotted onto nitrocellulose membranes. The membranes were blocked in 5% nonfat milk, 1% bovine serum albumin, and apoE was detected by ECL kit (Amersham Biosciences) as previously described (24,25). Signals on immunoblot were quantitated using Zero DScan software (Scanalytics Inc., Fairfax, VA).…”
Section: Methodsmentioning
confidence: 99%